Short‐ and medium‐term outcomes for patent ductus arteriosus stenting in neonates ≤2.5 kg with duct‐dependent pulmonary circulation. Issue 4 (29th July 2022) - Nasef, Mohamed Al; Shahbah, Doaa A.; Batlivala, Sarosh P.; Darwich, Reem; Qureshi, Athar M.; Breatnach, Colm R.; Linnane, Niall; Walsh, Kevin P.; Oslizlok, Paul; McCrossan, Brian; Momenah, Tarek; Alshahri, Atif; et al.
Abstract: Background: Morbidity with surgical systemic‐to‐pulmonary artery shunting (SPS) in infants ≤2.5 kg has remained high. Patent ductus arteriosus (PDA) stenting may be a valid alternative. The objective of this study is to evaluate outcomes following PDA stenting in patients ≤2.5 kg from four large tertiary centers. Methods: Retrospective review of all neonates ≤2.5 kg with duct‐dependent pulmonary circulation who underwent PDA stenting. Procedural details, pulmonary arterial growth, reinterventions, surgery type, and outcomes were assessed. Results: PDA stents were implanted in 37 of 38 patients attempted (18 female) at a median procedural weight of 2.2 kg (interquartile range [IQR], 2–2.4 kg). Seven patients (18%) had a genetic abnormality and 16 (42%) had associated comorbidities. The median intensive care unit stay was 4 days (IQR, 2–6.75 days), and the median hospital stay was 20 days (IQR, 16–57.25). One patient required a rescue shunt procedure, with three others requiring early SPS (<30 days postprocedure). Twenty patients (54%) required reintervention with either balloon angioplasty, restenting, or both. At 6‐month follow‐up, right pulmonary artery growth (median z ‐score −1.16 to 0.01, p = 0.05) was greater than the left pulmonary artery (median z ‐score −0.9 to −0.64, p = 0.35). Serious adverse effects (SAEs) were seen in 18% ( N = 7) of our cohort. One patient developed an SAE during planned reintervention There were no intraprocedural deaths, with one early procedure‐related mortality, and three interstage mortalities not directly related to PDA stenting. Conclusions: PDA stenting in infants ≤2.5 kg is feasible and effective, promoting pulmonary artery growth. Reintervention rates are relatively high, though many are planned to allow for optimal growth before a definitive operation.